2015
DOI: 10.21829/myb.2015.210424
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of chemical compositions, air-dry, preservation and workability of eight fastgrowing plantation species in Costa Rica

Abstract: Evaluación de la composición química, secado al aire, preservación y trabajabilidad de ocho especies de rápido crecimiento en plantación de Costa Rica AbstrAct Costa Rica has successfully planted various forestry species for wood production. However, the use of their wood is limited, due to poor knowledge about their chemical properties, air-dry, preserved and workability performance. The present study details information of these properties for the species: Alnus acuminata (Aa), Acacia mangium (Am), Bombacops… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 20 publications
1
5
3
Order By: Relevance
“…The values found for physical properties (SG, MC-G, GD, TS, and RS) and the different mechanical properties studied (MOR and MOE in bending test, compression stress, shear stress, and Janka hardness) for the different origins (Figure 3) and the different families (Table 2) of 8-yearold D. panamensis present some differences from those reported by Tenorio et al [22] for D. panamensis trees from 13-year-old plantations. For example, these authors report higher values of SG, MC-G, GD, TS, and RS than those found in this study (Table 2), resulting in higher mechanical property values in the wood of Tenorio et al [22]. On the other hand, the highest values of SG, GD, RT, and TS were reported for wood from trees growing in a natural forest [23], values higher than those obtained in this study for the different provenances (Figure 2) and the different families (Table 2).…”
Section: Morphological Physical and Mechanical Propertiescontrasting
confidence: 69%
See 2 more Smart Citations
“…The values found for physical properties (SG, MC-G, GD, TS, and RS) and the different mechanical properties studied (MOR and MOE in bending test, compression stress, shear stress, and Janka hardness) for the different origins (Figure 3) and the different families (Table 2) of 8-yearold D. panamensis present some differences from those reported by Tenorio et al [22] for D. panamensis trees from 13-year-old plantations. For example, these authors report higher values of SG, MC-G, GD, TS, and RS than those found in this study (Table 2), resulting in higher mechanical property values in the wood of Tenorio et al [22]. On the other hand, the highest values of SG, GD, RT, and TS were reported for wood from trees growing in a natural forest [23], values higher than those obtained in this study for the different provenances (Figure 2) and the different families (Table 2).…”
Section: Morphological Physical and Mechanical Propertiescontrasting
confidence: 69%
“…The values of BP, HWP, and SWP found for the different families (Table 1) are lower than those reported by Tenorio et al [22] for D. panamensis trees. The values found for physical properties (SG, MC-G, GD, TS, and RS) and the different mechanical properties studied (MOR and MOE in bending test, compression stress, shear stress, and Janka hardness) for the different origins (Figure 3) and the different families (Table 2) of 8-yearold D. panamensis present some differences from those reported by Tenorio et al [22] for D. panamensis trees from 13-year-old plantations. For example, these authors report higher values of SG, MC-G, GD, TS, and RS than those found in this study (Table 2), resulting in higher mechanical property values in the wood of Tenorio et al [22].…”
Section: Morphological Physical and Mechanical Propertiescontrasting
confidence: 68%
See 1 more Smart Citation
“…Sapwood, originating from nine Costa Rican fast-growing plantation species, was utilised in the work. It is well established that only sapwood of these tropical hardwood species has a good permeability [25,36,37]. Species used included Cedrela odorata, Cordia alliodora, Enterolobium cyclocarpum, Gmelina arborea, Hieronyma alchorneoides, Samanea saman, Tectona grandis, Vochysia ferruginea and Vochysia guatemalensis.…”
Section: Methodology Materialsmentioning
confidence: 99%
“…Furthermore, a great variety of species has been planted as part of the reforestation activities in Costa Rica, resulting in an important contribution to the lumber market (Tuk, 2010;Moya et al, 2015;. Mechanical properties of G. arborea lumber are among the most extensively studied in Costa Rica and their great potential has been demonstrated for uses such as structural components , in lumber, and other specifi c uses (Tenorio et al, 2011;Tenorio, 2012).…”
Section: Introduction 1 Uvodmentioning
confidence: 99%